Effects of Non-Coding RNA on Regulatory T Cells and Implications for Treatment of Immunological Diseases - Luo, Yuanhanyu; Wang, Honglin (Frontiers in Immunology, 2020)
Regulatory T cells (Tregs) are essential for regulating immune reactions and maintaining immune homeostasis. Non-coding RNAs (ncRNAs), including microRNAs and long non-coding RNAs, usually do not encode proteins but regulate intracellular biological processes at post-transcriptional levels. These ncRNAs have been demonstrated as key post-transcriptional regulators in the commitment of Tregs lineage and the plasticity of Tregs function. These ncRNAs can further be manipulated to benefit human immunological disorders caused by Tregs dysfunction. This review summarizes the effects of ncRNAs on Tregs and their potentials to be targets or approaches for the treatment of immunological diseases involving Tregs.